(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
After centuries of science and disciplines directed toward helping people, we have a new movement named Positive psychology. It is a result of ignoring important questions about wellbeing and strengths in scientific psychology. Positive psychology is scientific approach in research of positive emotions and experiences, development of positive traits and strengths, and application of findings in development and enabling positive institutions. Dedicated to those subjects, Positive psychology has a future. The future is seen in fulfillment of its essence and mission in every sphere of psychology, science and public life in general. But Positive psychology has a future only as a movement and platform, without pretensions for hard structure and strict problem of research.